Persepsi Fairness dalam Romantic Relationship pada Perempuan Emerging Adulthood - Permana, Muhammad Zein; Putri, Ferren Azzahra (Jurnal Wanita dan Keluarga, 2024)
This research aims to explore the perceptions of emerging adult women (aged 18-25 years) regarding fairness in Romantic Relationships. A total of 243 participants with an average age of 18 years (M = 22.5) answered open-ended questions about their perceptions of fairness in Romantic Relationships. The interview results were then analyzed thematically and categorized to obtain themes related to fairness in Romantic Relationships. Through qualitative methods with thematic analysis, it was found that fairness in Romantic Relationships is perceived when: 1) There is reciprocity, meaning the relationship is mutual or two-way; 2) There are shared goals; 3) There is equity or fairness, indicating that treatment in the relationship can be predicted; 4) There is no discrimination, meaning there is no differential or special treatment due to certain factors such as gender; 5) There is self-awareness, meaning both parties are aware of fulfilling their rights and obligations. These five themes appear to be in different psychological explanation domains, namely personal, interpersonal or relational, group, and even intergroup. These findings demonstrate the novelty of the fairness concept, which makes it understandable that research and interventions on fairness in romantic relationships have not yet been successful. This is because fairness concepts have been explained only in the interpersonal or relational domain so far, whereas this research finding indicates three other interconnected explanation domains that define the fairness concept in romantic relationships.